Corrosion Studies on SS-321 in Sodium-Chloride Solution Medium - Effendi, Nurdin; Wihatmoko, Wihatmoko; Jahja, Aziz K. (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Corrosion Studies on SS-321 in Sodium-Chloride Solution Medium. Experimentalcorrosion studies on commercial SS-321 have been carried out. The experiments were carried out in asodium chloride medium with a concentration variation of 0.4 mol. 0.5 mol, 0.6 mol, and 0.7 molcorresponding topH values of 7.0, respectively. The experiments were carried out using a type ofM-273EG&G potentiostat/galvanometer test instrument. The post-corrosion samples microstructure wereanalyzed with the aid of EDS (energy dispersive spectroscopy) equipped SEM instrument to detect thepresence of any viable corrosion byproducts. Forfurther verification x-ray diffraction method was alsoused to detect anypossible emerging corrosion byproducts on the samples surfaces. Experimentalresultsconfirm that AISl-321 commercial alloys immersed in a sodium chloride corrosion medium with avariation of concentration experience very little or almost no corrosion, and that according to the socalledFontana s criteria these test-materials turn out to have an excellent resistance toward sodiumchloriccorrosion. This is also evidenced by the very low corrosion rate value measured in this study.EDSstudy and X-ray diffraction results indicate that thepossible ensuing corrosion byproducts are ironoxides, chrome oxides, iron chlorides, and nickel hydrideoxide.